Pelatihan Penyusunan Rencana Kerja Pemerintah Desa (RKPDes) - Santi Merlinda; Ermita Yusida; Muhammad Hasyim Ibnu Abbas; Agus Sumanto (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities in the form of assistance and training for the preparation of RKPDes for government and community elements in Benjor Village aim to improve comprehensive development planning to achieve development goals. The method used was dissemination and training from the implementation team accompanied by practical activity programming. The results achieved in this activity were implementing training activities and assistance for the preparation of the RKP for Benjor Village. Through this activity, the participant's understanding of the preparation of the RKPDes increased, as evidenced by the ability to formulate programs and activities with targets based on development priorities. Additionally, there was also criticism of the 2020 planning document in this activity, which could be used as input for the development planning document for the following year. Overall, most of the participants stated that this training was helpful and that assistance was needed to prepare the RKPDes.